Unsupervised detection of disturbances in 2D radiographs - Estacio L. (2021)
This work was supported by grant 234-2015-FONDECYT (Master Program) from Cienciactiva of CONCYTEC-PERU and German BMBF research campus MODAL (grant no. 3FO18501). The authors thank CiTeSoft-UNSA for the database access. The authors report no conflicts of interest.